Legal Effectiveness Legal effectiveness of Electronic Land Certificate Issuance under the PTSL Program in Luwu Regency - Rini Kartini; Muhammad Sabir Rahman; Ardiyanti Aris; Bakhtiar Tijjang; Kairuddin Kairuddin (Priviet Social Sciences Journal, 2026)
This study aims to analyze the legal effectiveness of electronic land certificate issuance under the Complete Systematic Land Registration (PTSL) Program in Luwu Regency and to identify the factors supporting its implementation. The transition from analog to electronic certificates represents a strategic effort by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) to modernize land administration and strengthen legal certainty over land rights. This research employed normative-empirical legal research with a qualitative approach. Data were collected through observations, interviews, and documentation at the Luwu Regency Land Office. The analysis used Soerjono Soekanto’s theory of legal effectiveness, consisting of legal factors, law enforcement factors, facilities and infrastructure, community factors, and cultural factors. The findings indicate that the implementation of electronic land certificate issuance under the PTSL Program in Luwu Regency was effective and successfully achieved the 2024 target of 11,200 certificates. Supporting factors included comprehensive technical guidelines, adaptive human resources, adequate digital facilities and infrastructure, effective coordination between the Land Office and village governments, and strong leadership supervision. Although the transition initially created technical and administrative challenges, the local community generally accepted the electronic certificate system. This study demonstrates that electronic land certification can improve efficiency and legal certainty in land registration services. Keywords: electronic land certificate, PTSL, legal effectiveness, land registration, legal certainty, digitalization